Intercropping of corn and bean in different plant arrangements and population, in Pelotas, RS - Raposo, João Antonio de Arruda; Schuch, Luis Osmar Braga; de Assis, Francisco Neto; Machado, Amauri Almeida (Pesquisa Agropecuaria Brasileira, 1995)
An intercropping experiment was made with corn (cv. Pioneer 6874) and bean (cv. Rio Tibagi) planted simultaneously, in Pelotas, RS, Brazil, using the following four plant arrangements: (a) corn and bean in the same row; (b) corn and bean in alternated rows; (c) two rows of corn for two rows of bean; (d) two rows of corn for three rows of bean, all combined with corn plant populations of 30,000, 40,000 and 50,000 plants/ha. The bean had always 200,000 plants/ha. These were compared with monocrops of corn and bean. The results showed that plant arrangements influenced grain yield significantly on both cultures. When intercropped, these cultures decreased grain yield in 18.7% and 52.2% compared to corn and bean isolated, respectively. The corn plant survival was affected by its population and plant arrangement, which did not occur to the bean plant survival. The intercropping system showed advantages in relation to LER (Land Equivalent Ratio). The highest rates were achieved with the arrangement of alternated rows.